Evaluation of Breastfeeding as an Analgesic Intervention in Neonates Undergoing Heel Prick: A Randomized Controlled Study - Pahwa, Gunjeet Kaur; Rathore, Virendra Singh; Meena, Shiv Singh; Sharma, Gopi Kishan (Journal of Neonatal Surgery, 2025)
Background: Heel pricks in neonates cause significant pain and stress, with potential adverse outcomes. Pharmacological analgesics are limited, so non-pharmacological methods are vital. Breastfeeding offers safe analgesia through maternal contact, suckling, and sweet taste. Pain can be assessed using the Premature Infant Pain Profile (PIPP). Objective: To assess the analgesic effectiveness of breastfeeding during painful procedures in neonates using the Premature Infant Pain Profile (PIPP) scoring system. Methods: A randomized controlled trial was conducted at JK Lon Mother and Child Hospital, KOTA, from January 2022 to December 2022. One hundred neonates (51 males, 49 females) with gestational age ≥34 weeks requiring heel prick for blood sugar monitoring were randomized into two equal groups: Group A (without breastfeeding, n=50) and Group B (with breastfeeding, n=50). Pain assessment was performed using PIPP scoring system before, during, and after the procedure. Results: The study demonstrated significant differences in pain perception between groups. In the breastfeeding group, 74% of neonates experienced no pain compared to only 20% in the non-breastfeeding group. Severe pain was observed in 14% of neonates without breastfeeding, while none in the breastfeeding group experienced severe pain. The relative risk was 0.351 (95% CI: 0.203-0.607, p<0.0001), and odds ratio was 0.087 (95% CI: 0.034-0.223, p<0.0001). Conclusion: Breastfeeding serves as an effective non-pharmacological analgesic intervention during painful procedures in neonates, significantly reducing pain perception as measured by PIPP scoring